PENGARUH PROFITABLITAS, SOLVABILITAS, OPINI AUDIT DAN UKURAN PERUSAHAAN TERHADAP AUDIT REPORT LAG - Anisa Fu’adiyah; Dirvi Surya Abbas; Hamdani, Hamdani; Ahmad Jayanih (Pusat Riset dan Inovasi Nasional, 2022)
This study aims to test and provide empirical evidence about the effect of profitability, solvency, audit opinion and firm size on audit report lag on transportation companies listed on the IDX for the period 2016 – 2021. With a total sample of 15 companies with a period of 6 years, 90 samples were obtained. observed. The analysis method of this research uses panel data regression through software eviews 12. The results show that firm solvency has a positive effect on audit report lag while profitability, audit opinion and firm size have no effect on audit report lag.